Examining the moderating role of gang involvement on the context and impact of victimization. Issue 2 (13th June 2016) - Kubik, Joanna; Docherty, Meagan; Boxer, Paul; Veysey, Bonita; Ostermann, Michael
Abstract : Purpose: – Research suggests that gang-involved youth are more likely than non-gang youth to experience victimization. However, very little research has addressed the issue of whether the relationship between gang involvement and victimization depends on the context in which victimization takes place. The purpose of this paper is to examine the nature of the relation between gang involvement and violent victimization in both street and school contexts. Design/methodology/approach: – Data were provided by youth (n=421; ages 11-18; 70 percent male; 66 percent non-white) referred by the justice system for intensive home and community-based treatment of problem behavior. At intake, youth reported on their experiences of violent victimization, mental health status, problem behavior, and substance use. Youth and therapist reports were utilized to indicate gang involvement. Findings: – Approximately 62 percent of gang-involved youth in the sample were victimized across both contexts. Linear and censored regression models found that on average, gang-involved youth experienced a greater frequency of victimization than non-gang youth (p < 0.001). Importantly, results also show that gang involvement amplifies the impact of victimization on key behavioral and mental health outcomes. Victimization in both street and school contexts increases the risk of serious problem behavior for gang-involved youth (p < 0.001). Victimization experiences in schools in particular also may increase alcohol use among gang-involved youth (p=0.006). Originality/value: – These findings emanating from a unique sample of youth in treatment demonstrate the value of considering victimization in context for intervention programming.